Characterization of Ocular Biomechanics in Pellucid Marginal Degeneration. Issue 4 (April 2016) - Lenk, Janine; Haustein, Michael; Terai, Naim; Spoerl, Eberhard; Raiskup, Frederik
Abstract : Purpose: This study sought to investigate the diagnostic capacity of corneal biomechanical response parameters in a group of patients with pellucid marginal degeneration (PMD) using the Ocular Response Analyzer (ORA) and Corvis ST devices. Methods: In this prospective clinical study, we used the Corvis ST and ORA devices to investigate the ocular biomechanics of patients with PMD. Eighty-one eyes were included, and 2 study groups were formed: the PMD group (the study group, n = 29) and the control group (n = 52). We focused on 13 biomechanical parameters. Statistical analysis was performed using SPSS. Biomechanical parameters for the 2 groups were compared using analysis of covariance. Results: The ORA results demonstrated that the Keratoconus Match Index was significantly lower in the PMD group than in the control group (0.031 ± 0.37 vs. 0.79 ± 0.33; P = 0.001). The 2 groups did not significantly differ with respect to intraocular pressure– and central corneal thickness–adjusted values for corneal hysteresis or corneal resistance factor. Regarding the Corvis parameters, differences between the control and PMD groups were detected for CorWmax amp (control 1.01 ± 0.01, PMD 1.06 ± 0.01; P = 0.020) and CorA2 t (control 21.78 ± 0.03, PMD 21.66 ± 0.04; P = 0.0003). Conclusions: We identified 2 Corvis parameters that could be used to characterize PMD and differentiate PMD corneas from normal corneas. These parameters support the hypothesis that there is significantly less deformation of the central cornea in PMD corneas than in healthy corneas. However, because useful "first-line" diagnostic devices for diagnosing PMD (such as Pentacam and the ORA) exist, the Corvis ST serves as an additional diagnostic tool that can also be used for long-term monitoring after diagnosis confirmation.